Prevalence of Sarcopenic Obesity in Various Comorbidities, Diagnostic Markers, and Therapeutic Approaches: A Review - Mangalam Kumari; Archana Khanna (Annals of Geriatric Medicine and Research, 2022)
The coexistence of sarcopenia and obesity characterizes sarcopenic obesity. In this condition, there is an imbalance between lean and fat mass amounts. It is a prevalent issue that is gaining prevalence among the elderly population. To evaluate the condition, allied health professionals may employ non-invasive diagnostic techniques, such as gait speed, skeletal muscle mass, and muscle strength. Nevertheless, early diagnosis and treatment of pathology are essential for preventing debilitating effects and providing the highest quality of care. This article reviews the prevalence of sarcopenic obesity in numerous medical conditions, such as cancer, arthritis, postoperative cases, diabetes mellitus, obesity, and metabolic syndrome. In addition, this paper aims to examine the available evidence regarding the prevalence of sarcopenic obesity in other conditions along with their diagnostic markers and therapeutic approaches.